Assessing a novel problem‐based learning approach with game elements in a business analytics course. (9th June 2021) - Bayley, Tiffany; Wheatley, David; Hurst, Ada
Abstract: Business education has traditionally relied on case‐based learning as its main form of active learning. However, this method is not always appropriate in introductory undergraduate business analytics courses, which require students to first master analytical techniques, best taught through examples of numerical problems. Building on established problem‐based learning (PBL) pedagogy, we propose a new approach in which students solve well‐structured problems in a gamified environment. The learner is challenged to solve a series of numerical problems at their own pace in a self‐directed manner. The series of problems are designed such that the student must find the correct solution to the first problem to unlock and progress to the next problem, and so on. To assess our method, both student outcomes and experience were evaluated in a controlled study that compared it to traditional lecturing. While student outcomes were similar, students perceived traditional lectures as more effective. Our results indicate that the game elements in our approach did not sufficiently increase student engagement to counteract negative student perceptions of PBL, which are well‐documented in the literature. We conclude with a discussion of advantages and drawbacks of this new approach, considerations for adapting it to virtual settings, and opportunities for expanding game elements to increase student engagement.